El impacto y la evolución de la virtualidad en los procesos judiciales laborales - Abanto Revilla, César (Pontificia Universidad Católica del Perú, 2023)
This essay critically reviews the measures that the Judiciary has taken, as a result of digitalization derived (and accelerated) by the arrival of COVID-19, which has generated a race for comprehensive implementation, at the national level. national: of the Electronic Judicial Record (EJE), the Electronic Notification System (SINOE), among other technological tools, such as the Virtual Hearing, whose application in Labor Headquarters has originated positions for and against its validity and procedural legitimacy. In this sense, it is reviewed if these measures have affected the implementation of the labor procedural reform of 2010, based on orality and the use of technologies, but also accounting for the questioning of unfulfilled promises, which are based on an apparent disconnection of the objectives of the change and the tasks that each participant in the conflictive relationship should fulfill.

En el presente ensayo se revisa, en tono crítico, las medidas que ha tomado el Poder Judicial, producto de la digitalización derivada (y acelerada) por la llegada de la COVID-19, que ha generado una carrera por la implementación integral, a nivel nacional: Del Expediente Judicial Electrónico (EJE), el Sistema de Notificaciones Electrónicas (SINOE), entre otras herramientas tecnológicas, como la Audiencia Virtual, cuya aplicación en Sede Laboral ha originado posturas a favor y en contra de su validez y legitimidad procesal. En tal sentido, se revisa si dichas medidas han afectado la implementación de la reforma procesal laboral del 2010, basada en la oralidad y el uso de las tecnologías, pero dando cuenta también de los cuestionamientos a promesas incumplidas, que parten de una desconexión aparente de los objetivos del cambio y las labores que cada partícipe de la relación conflictual debería cumplir.
The impact and evolution of virtuality in the labor judicial process
Keywords: Labor Process; Virtualization; Orality; Immediacy; Flexibility; Proceso Laboral; Virtualización; Oralidad; Inmediación; Flexibilidad; https://purl.org/pe-repo/ocde/ford#5.05.00